Basal bodies in Xenopus. Issue 1 (December 2015) - Zhang, Siwei; Mitchell, Brian
Abstract Xenopus has been one of the earliest and most important vertebrate model organisms for investigating the role and structure of basal bodies. Early transmission electron microscopy studies inXenopus revealed the fine structures ofXenopus basal bodies and their accessory structures. Subsequent investigations using multiciliated cells in theXenopus epidermis have further revealed many important features regarding the transcriptional regulation of basal body amplification as well as the regulation of basal body/cilia polarity. Future basal body research usingXenopus is expected to focus on the application of modern genome editing techniques (CRISPR/TALEN) to characterize the components of basal body proteins and their molecular functions.